Functionalized magnetite-biochar with live and dead bacteria for adsorption-biosorption of highly toxic metals: Cd, Hg, and Pb - Yudha Gusti Wibowo; Dedy Anwar; Hana Safitri; Indra Surya; Sudibyo Sudibyo; Ahmad Tawfiequrrahman Yuliansyah; Himawan Tri Bayu Murti Petrus (Next Materials, 2025)
Environmental pollution by heavy metals such as cadmium (Cd), mercury (Hg), and lead (Pb) poses severe risks to ecological and human health. Conventional remediation technologies often fall short in efficacy and sustainability. This study explores a novel hybrid system combining functionalized magnetite-biochar with live and dead bacteria for enhanced adsorption-biosorption of these contaminants from wastewater. The synergy of magnetite-biochar and bacterial biomass exploits the high adsorption capacity of the composite and the unique biosorptive abilities of bacteria, offering a dual mechanism for metal removal. The composite's effectiveness was assessed through comparative studies, demonstrating superior removal efficiencies and operational advantages over traditional methods. Key findings include the composite's ability to function effectively across a broad range of environmental conditions and its potential for regeneration and reuse, highlighting its suitability for scalable applications. This research not only presents a viable alternative to existing wastewater treatment technologies but also aligns with sustainable practices by minimizing environmental impact and reducing treatment costs. The promising results suggest significant potential for the practical deployment of this technology in mitigating heavy metal pollution, urging further development towards commercialization and industrial use. The integration of such innovative materials could revolutionize wastewater treatment strategies and contribute to global sustainability efforts in pollution control.